A modal approach for shape defect measurement based on global stereocorrelation. (May 2020) - Etievant, David; Quinsat, Yann; Thiebaut, François; Hild, François
Highlights: Development of a shape defect measurement technique using stereocorrelation. Shape correction based on a modal basis to reduce the number of unknowns. Application on a test part and comparison with an industrial measurement system. Study of the repeatability of the method. Sensitivity analysis of the measurement method based on the Hessian matrix analysis. Abstract: The metrology of mechanical parts using non-contact systems often requires complex post-processing operations to evaluate shape defects of the studied surface. For large parts, the geometric complexity combined with the amount of acquired data make such treatments long and tedious. To overcome this challenge, a shape defect measurement system based on global stereocorrelation is developed. This approach integrates a self-calibration step using the CAD model of the studied part that allows the measurement results to be directly expressed in the numerically defined frame of the part. The defects will be measured in a predefined modal basis, thereby introducing registrations with a limited number of degrees of freedom and allowing for easier analyses of the measured defects.